Barriers and Facilitators to Physical Activity for People With Scleroderma: A Scleroderma Patient‐Centered Intervention Network Cohort Study. Issue 8 (11th May 2022) - Harb, Sami; Peláez, Sandra; Carrier, Marie‐Eve; Kwakkenbos, Linda; Bartlett, Susan J.; Hudson, Marie; Mouthon, Luc; Sauvé, Maureen; Welling, Joep; Shrier, Ian; Thombs, Brett D.; ,
Abstract : Objective: To support physical activity among people with systemic sclerosis (SSc [scleroderma]), we sought to determine the prevalence and importance of barriers and the likelihood of using possible facilitators. Methods: We invited 1, 707 participants from an international SSc cohort to rate the importance of 20 barriers (14 medical, 4 social or personal, 1 lifestyle, and 1 environmental) and the likelihood of using 91 corresponding barrier‐specific and 12 general facilitators. Results: Among 721 respondents, 13 barriers were experienced by ≥25% of participants, including 2 barriers (fatigue and Raynaud's phenomenon) rated "important" or "very important" by ≥50% of participants, 7 barriers (joint stiffness and contractures, shortness of breath, gastrointestinal problems, difficulty grasping, pain, muscle weakness and mobility limitations, and low motivation) by 26–50%, and 4 barriers by <26%. Overall, 23 of 103 facilitators (18 medical‐related) were rated by ≥75% of participants as "likely" or "very likely" to use among those who experienced corresponding barriers. These facilitators focused on adapting exercise (e.g., using controlled, slow movement), taking care of one's body (e.g., stretching), keeping warm (e.g., wearing gloves), and protecting skin (e.g., covering ulcers). Among those participants who had previously tried the facilitator, all facilitators were rated by ≥50% as "likely" or "very likely" to use. Among those participants with the barrier who had not tried the facilitator, only 12 of 103 facilitators were rated by >50% of participants as "likely" or "very likely" to use. Conclusion: Medical‐related physical activity barriers were common and considered important. Facilitators considered as most likely to be used involved adapting exercise, taking care of one's body, keeping warm, and protecting skin.